SOIL SEED BANK AS A BIOINDICATOR TO IDENTIFY INVASIVE SPECIES - Silva, Ariane Cristine Araujo; Martins, Sebastião Venâncio; Balestrin, Diego (Floresta, 2021)
This study aimed to characterize the soil seed bank in an area dominated by Leucaena leucocephala, here called “Povoamento de Leucaena” (PL) and an area of native forest in the Parque Estadual do Rio Doce (PERD), both of which are affected by the city of Ipatinga, MG. Thirty sample units (SU) with dimensions of 25.0 x 25.0 x 5.0 cm were installed in each of the study areas and the seed bank of the areas was collected and evaluated. The emerging seedlings were counted and identified; the evaluations were carried out weekly during the six-month period. The average density of germinated seeds was 716.2 seeds/m² in the PL and 86.4 seeds/m² in the PERD area. In addition, 39 species were identified in the PL area (41% exotic), while in the PERD area 32 species were identified (25% exotic). The exotic tree species that stood out in number of individuals were Muntingia calabura and L. leucocephala, representing 82.57% and 5.88%, respectively of the total individuals found. Therefore, both environments are under strong environmental pressure, requiring the control of existing exotic species, as well as enrichment actions with the planting of species of diversity to accelerate the restoration process in the PL area.